2016
DOI: 10.3892/etm.2016.3939
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic epithelial proliferation is correlated with COX-2 expression in dentigerous cyst and ameloblastoma

Abstract: Abstract. Investigation of cyclooxygenase (COX)-2 in dentigerous cyst and ameloblastoma may help to improve understanding of the nature and behavior of odontogenic cysts and tumors, and in addition may eventually represent a definitive target for a pharmacological approach in the management of these lesions. The aim of this study was to evaluate COX-2 expression and its correlation with the proliferation of odontogenic epithelium in these lesions. Dentigerous cysts (n=16) and ameloblastomas (n=17) were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Wassem et al (16) concluded that activation and proliferation of keratinocytes result in downregulation of K15. Our previous studies showed the non-different expression of proliferating epithelial cells in OKC and AB (17,18). This may explain the similar expression of K15 in odontogenic epithelium of both OKC and AB in the current study.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Wassem et al (16) concluded that activation and proliferation of keratinocytes result in downregulation of K15. Our previous studies showed the non-different expression of proliferating epithelial cells in OKC and AB (17,18). This may explain the similar expression of K15 in odontogenic epithelium of both OKC and AB in the current study.…”
Section: Discussionsupporting
confidence: 62%
“…The current study, as many previous reports (9)(10)(11)(12)15,17,18) excluded the use of control group samples in the study of odontogenic lesions. This is because no true tissue equivalent exists to serve as a negative control, as odontogenic lesions encompass reactive tissues and tumors which replace the healthy bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial-mesenchymal transition was found to be related to the local invasiveness of ameloblastoma, with upregulation of Slug and TGFβ and reduced E-cadherin expression (Kurioka et al 2017). COX-2 (cyclooxygenase 2) expression correlates with odontogenic epithelial proliferation in ameloblastoma, which may contribute to local invasion (Alsaegh et al 2017). CK15 and CK16 were stained positive in follicular but not plexiform ameloblastomas (Wato et al 2006).…”
mentioning
confidence: 99%
“…Cyclooxygenase (Cox)-2 is a cytokine-inducible enzyme that is present in the nuclear membrane and luminal side of the endoplasmic reticulum ( 9 ). It has been reported as a pivotal factor in multiple physiological functions and pathological processes, including inflammation and tumorigenesis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%